Novel green synthesis of silver nanoparticles from empty fruit bunch waste: Biomedical applications and mechanistic insights - Bashirat Olamide Yusuf-Salihu; Shakirat Afodun Abdulmumini; Toheeb Taiye Bajepade; Halimah Adekunbi Durosinmi; Muinat Olanike Kazeem; Victoria Atinuke Ajayi; Agbaje Lateef (Next Nanotechnology)
Agricultural waste, such as empty fruit bunches (EFB) from palm oil production, poses environmental and health risks if not effectively managed. This study addresses this issue by innovatively transforming EFB biomass into high-value silver nanoparticles (AgNPs) via a green synthesis approach, marking the first successful biosynthesis of AgNPs from EFB. UV-Vis, FTIR, TEM, SAED, and EDX studies were used to characterize biosynthesized EFB-AgNPs. Biosynthesized EFB-AgNPs were tested for antibacterial, antioxidant, antidiabetic, anticoagulant, and thrombolytic activities. EFB-AgNPs showed a surface plasmon resonance peak at 477 nm, hydroxyl and amine group stabilization, and a silver content of 75.56 %. TEM and SAED analyses confirmed nanoscale particle diameters ranging from 12.78 nm to 19.10 nm, with a characteristic face-centered cubic (FCC) crystalline structure. EFB-AgNPs inhibited Escherichia coli, Klebsiella oxytoca, Staphylococcus aureus, Proteus mirabilis, and Pseudomonas aeruginosa dose-dependently from 40 % to 80 %, and 100 % of Aspergillus niger, A. fumigatus, and A. flavus. Reactive oxygen species (ROS) may cause cell membrane rupture and oxidative stress. Antioxidant testing demonstrated concentration-dependent activity across multiple assays: DPPH scavenging reached 81.49 % at 160 µg/ml, ferric-reducing activity was 90.05 % at 150 µg/ml, H₂O₂ scavenging achieved 91.00 % at 80 µg/ml, and NO scavenging reached 83.43 % at 150 µg/ml. Furthermore, EFB-AgNPs prevented blood coagulation and dissolved blood clots. In addition, EFB-AgNPs inhibited α-amylase with 74.64 % at 100 µg/ml. This unique approach of transforming EFB trash into high-value AgNPs could help sustain waste management and the circular bioeconomy by enabling medicinal applications.